Indicadores de gestão de resíduos sólidos urbanos: uma visão voltada à sustentabilidade - Silva, Luciana da (2017)
With the implementation of the National Solid Waste Policy in Brazil, in 2010, based on the principles of sustainability, it is fundamental that municipalities have subsidies for their implementation, as well as for the integrated management of solid urban waste efficiently. Inefficiency in this management, which is caused by several factors, including the lack of adequate or poor quality indicators for local application, generates a number of problems in urban areas, such as the accumulation of waste in inappropriate or public areas, causing visual pollution, obstruction of the drainage system, contamination of rivers and streams, disease spread, pollution of air, soil, and groundwater, etc. These problems have a direct impact on the environment, health, and quality of life, so there is a need for a system of indicators that is appropriate to the local reality, allowing efficient management and sustainable governance. Thus, this study describes the current situation of urban solid waste management (MSWM) in the cities of Passo Fundo, Santa Maria, and Porto Alegre, in the State of Rio Grande do Sul; investigates and compares the latest proposals for national indicator systems and international standards for MSWM; and select among them a set of indicators to evaluate the sustainability of the MSWM. In order to select the indicators, the following research approaches were used: content analysis techniques; selection by the adapted management excellence model (MEG); on-line survey with national and international stakeholders; focus groups with local stakeholders; and a method based on selection and exclusion criteria . The result of the analysis of a set of 396 indicators, grouped by dimensions of sustainability and categorization, generated a subset of 49 indicators. However, due to the lack of data, it was not possible to quantify the 49 selected indicators, which did not allow the necessary reliability for its use in a MSWM sustainability assessment method, evidencing the fragility of the MSWM information system. Therefore, for the sustainability assessment of the MSWM, the Urban Cleaning Sustainability Index (UCSI) was applied, from which municipalities are scored, classified, and compared. The results evidenced the urgent need for improvement of the municipal databases regarding MSWM indicators, especially in the medium-sized municipalities, which present the highest growth rates among Brazilian cities. In addition, there is a need to increase the subsidies and infrastructure for municipal waste management, without which it is impossible to meet the current demands for compliance with the National Solid Waste Policy and the Sustainable Development Objectives. As guidelines to municipalities for the implementation of indicators that guarantee the sustainability of the MSWM, it is recommended to include in the monitoring system, indicators related to the measurement of natural resources, as well as to prioritize the elaboration and conclusion of the municipal plans for integrated solid waste management, and to implement continuous environmental education programs and actions.